Design of a novel sextuple band-notched UWB antenna - Han LIU; Cheng-you YIN; Qi-meng FAN (Tongxin xuebao)
A novel sextuple band-notched UWB antenna was designed. Sextuple band-notched characteristics could be realized by adding a T-shaped stub, a bent stub, and etching a U-shaped slot on the patch, adding a C-shaped stub, an anti-C shaped stub near microstrip line and etching a pair of L-shaped slots on the ground plane,which effectively sup-presses the interference between narrow band systems and UWB systems. The influence of the proposed structures on band-notched characteristics was studied, and band-notched principle was explained by antenna surface current and equivalent circuit. Finally the antenna was fabricated and measured. The measured results of VSWR, radiation patterns and gains agree well with the simulated results, which demonstrates the correctness of the design method. The proposed antenna has good performance and can be widely used due to its sextuple band-notched characteristics.